Modern quantum mechanics - Sakurai, J. J.; Tuan, San Fu (New Delhi: Pearson Education, 1994)
his authoritative, modern introduction to quantum mechanics includes discussions of fundamental topics and newer developments and employs a direct approach to quantum systems and provides an immediate introduction to quantum formalism. Problems are integrated throughout the text. In this Revised Edition, degenerate time-independent perturbation theory has been reworked, and two supplements have been added on adiabatic change and geometrical phase (Berry phase) and non-exponential decays, to take into account developments in quantum mechanics which have become prominent since the original edition Salient Features The author was a noted theorist in particle physics and was well known in his area of expertise. This revised edition retains the original material, but adds topics that extend its relevance into the 21st centur Table Of Contents Fundamental Concepts Quantum Dynamics Theory of Angular Momentum Symmetry in Quantum Mechanics Approximation of Methods Identical Particles Scattering Theory
Index 499-508p.